Patient-reported symptoms in the detection of head and neck cancer recurrence: a systematic review - Hulse, Kate; Hurley, Rhona; Lowit, Anja; Maguire, Roma; Paterson, Claire; Douglas, Catriona M. (Frontiers in Oncology, 2025)
IntroductionPatient-initiated follow-up (PIFU) after treatment for head and neck cancer (HNC) relies on the signs and symptoms of recurrence being detectable by patients. We examine the evidence for patient-reported symptoms as an indicator of recurrence.MethodsA search was conducted via OvidMEDLINE and Embase (2010 to January 2024) plus sources of grey literature for studies which describe patient-reported symptoms and recurrent disease. Findings are reported as per PRISMA guidelines.ResultsTwenty studies were included which were highly heterogenous. The median sensitivity of patient-reported symptoms to detect recurrence is 47.3%. Median specificity, positive-predictive value (PPV) and negative-predictive value (NPV) were 79.3%, 9.3% and 98.0% respectively. New symptoms were generally reported at routine follow-up rather than expedited appointments.ConclusionThe high specificity and NPV of patient-reported symptoms means recurrence is unlikely in the absence of symptoms. Patient education and collection of prospective data through digital health technologies may increase the effectiveness of PIFU.